Diagnosis and Surveillance of Neonatal Infections by Metagenomic Next-Generation Sequencing - Zhang, Rong; Zhuang, Yan; Xiao, Zheng-hui; Li, Cai-yun; Zhang, Fan; Huang, Wei-qing; Zhang, Min; Peng, Xiao-Ming; Liu, Chao (Frontiers in Microbiology, 2022)
Microbial Infections cause significant morbidity and mortality in neonates. Metagenomic Next-Generation Sequencing is a hypothesis-free and culture-free test that enables broad identification of pathogens and antimicrobial resistance genes directly from clinical samples with a 24-hour turnaround time. In this study, we used mNGS for etiological diagnosis and monitoring the efficacy of antibiotic treatment in a cohort of neonatal patients with severe infections. The median age was 19.5 (3 - 52) days, median gestational age was 37.96 (31 - 40+3) weeks and median birth weight was 3261 (1300 - 4300) g. The types of infectious diseases included pneumonia, sepsis, and meningitis. mNGS reported microbial findings in all cases, which led to changes in antibiotic treatment. These included cases of Mycobacterium tuberculosis, Legionella pneumophila and Bacillus cereus. Eight of ten infants recovered after antibiotic adjustment and showed normal development during follow-up. On the other hand, neurological retardation was seen in two infants with meningitis. mNGS enabled etiological diagnosis and guided antibiotic therapy when all conventional methods failed to discover the culprit. It has the potential to cut down the overall cost and burden of disease management in neonatal infections.